Adult best friends [videorecording (DVD)] - Buffett, Delaney; Buffett, Delaney; Corwin, Katie; Corwin, Katie; Quinto, Zachary (Gravitas Ventures, 2025)
Katie and Delaney, inseparable from childhood, find their paths diverging in their 30s. When Katie's boyfriend proposes, she plans a nostalgic trip with Delaney, intending to soften the blow by sharing the news in a familiar setting.